Economic impact of trade agreements and the emerging international economic agenda : agriculture - Miner, William M. (Carleton University OttawaCA, 1993)
Assesses the economic impact of trade agreements, such as Canada-US Free Trade Agreement (FTA), the North American Free Trade Agreement (NAFTA), and the proposed Uruguay Round Agreement on Agriculture, on the Canadian economy and the agri-food sector.